The Effect of Government Subsidies, Infrastructure Development, and Fiscal Decentralization on Poverty Reduction in Rural Indonesia - Haryono, Haryono (Westscience Press, 2025)
This study examines the effect of government subsidies, infrastructure development, and fiscal decentralization on poverty reduction in rural Indonesia through a normative juridical analysis. The analysis highlights the role of legal frameworks in shaping these interventions and identifies the strengths and weaknesses of existing policies. Government subsidies, such as the Program Keluarga Harapan (PKH) and Raskin, have proven beneficial in providing direct financial support to vulnerable populations, but face challenges related to targeting, distribution, and corruption. Infrastructure development has improved access to markets and essential services, yet legal barriers such as land acquisition disputes and funding limitations hinder its full potential. Fiscal decentralization, while empowering local governments, suffers from revenue disparities and weak local governance structures that undermine its effectiveness. The study concludes that legal and institutional reforms are necessary to enhance the efficiency and reach of these poverty reduction measures, ensuring that resources are effectively allocated to rural areas in need.